Nanocarbon Allotropes-Graphene and Nanocrystalline Diamond-Promote Cell Proliferation - Verdanova, Martina; Rezek, Bohuslav; Broz, Antonin; Ukraintsev, Egor; Babchenko, Oleg; Artemenko, Anna; Izak, Tibor; Kromka, Alexander; Kalbac, Martin; Hubalek Kalbacova, Marie (Small (Weinheim an der Bergstrasse, Germany), 2016)
Two profoundly different carbon allotropes - nanocrystalline diamond and graphene - are of considerable interest from the viewpoint of a wide range of biomedical applications including implant coating, drug and gene delivery, cancer therapy, and biosensing. Osteoblast adhesion and proliferation on nanocrystalline diamond and graphene are compared under various conditions such as differences in wettability, topography, and the presence or absence of protein interlayers between cells and the substrate. The materials are characterized in detail by means of scanning electron microscopy, atomic force microscopy, photoelectron spectroscopy, Raman spectroscopy, and contact angle measurements. In vitro experiments have revealed a significantly higher degree of cell proliferation on graphene than on nanocrystalline diamond and a tissue culture polystyrene control material. Proliferation is promoted, in particular, by hydrophobic graphene with a large number of nanoscale wrinkles independent of the presence of a protein interlayer, i.e., substrate fouling is not a problematic issue in this respect. Nanowrinkled hydrophobic graphene, thus, exhibits superior characteristics for those biomedical applications where high cell proliferation is required under differing conditions.
Keywords: cell adhesion; Diamond; Cell Proliferation; Nanoparticles; Photoelectron Spectroscopy; graphene; nanočástice; grafit; Microscopy, Atomic Force; diamant; Graphite; mikroskopie atomárních sil; Stem Cells; kultivované buňky; lidé; fotoelektronová spektroskopie; Microscopy, Electron, Scanning; Humans; carbon allotropes; proliferace buněk; Cells, Cultured; nanocrystalline diamonds; mikroskopie elektronová rastrovací; cell proliferation; kmenové buňky